EDP ; controls and auditing - Porter, W. Thomas; Perry, William E. (Boston, Mass. : Kent Pub. Co., 1981)
In this new edition, we have incorporated material on foreign corrupt practices Act revised materials on flowcharting, expanded the materials on controls; added a new chapter (chapter 2) on information systems design, and completely revised chapter 12 on computerized audit techniques in addition, end-of-chapter problems and causes were added and revised as deemed appropriate.
Includes bibliographical references and index.
osa 21/01/2019
Loans
Keywords: Electronic data processing departments